2017
DOI: 10.1002/ps.4508
|View full text |Cite
|
Sign up to set email alerts
|

The toxicity of flonicamid to cotton leafhopper, Amrasca biguttula (Ishida), is by disruption of ingestion: an electropenetrography study

Abstract: We propose that starvation caused by inhibition of active ingestion is the mechanism of toxicity for flonicamid. This knowledge could aid in applicability and use of this new insecticide for field management of leafhopper populations. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Salivary gland specific knockdown of Kir1 gene or pharmacological inhibition of Kir1 channel leaded to a significant reduction of sucrose ingestion during D. melanogaster feeding 17 . Chemical inhibition of Kir channels also reduced the salivary secretion and feeding in Amblyomma americanum , Amrasca biguttula , Nilaparvata lugens and Aphis gossypii 4,8,35,45 . Our study found that knockdown of CsKir2B significantly reduced the weights of Chilo suppressalis larvae, which might be caused by the reduced feeding of larvae.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Salivary gland specific knockdown of Kir1 gene or pharmacological inhibition of Kir1 channel leaded to a significant reduction of sucrose ingestion during D. melanogaster feeding 17 . Chemical inhibition of Kir channels also reduced the salivary secretion and feeding in Amblyomma americanum , Amrasca biguttula , Nilaparvata lugens and Aphis gossypii 4,8,35,45 . Our study found that knockdown of CsKir2B significantly reduced the weights of Chilo suppressalis larvae, which might be caused by the reduced feeding of larvae.…”
Section: Discussionmentioning
confidence: 49%
“…4 The toxicity of flonicamid against cotton leafhopper Amrasca biguttula was relatively low with the LC 50 values of 595.71 and 239.22 mg L −1 at 3 and 5 days post-treatment, respectively. 35 The LC 50 of flonicamid against different populations of Bemisia tabaci ranged between 95.7 and 1001 mg L −1 at 9 days after treatment. 6 In China, flonicamid was registered in different crops for the control of aphids and planthoppers with a registered concentration of 100 to 200 mg L −1 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…[125][126][127][128] The antifeedant and growth regulator azadirachtin was one of the earliest targets of EPG research in aphids and leafhoppers, 111,129 along with flonicamid and pymetrozine in aphids, leafhoppers, and psyllids. 130,131 The latter compound, pymetrozine, blocks the transient receptor potential vanilloid (TRPV) channels of chordotonal organs, thus directly and selectively interfering with feeding behavior of sap-feeding insects, leading to their starvation. 132,133 By contrast, flonicamid inhibits inward rectifier potassium (Kir) channels of epithelial and glandular systems, compromising salivary activity and fluid-feeding.…”
Section: Epg and Chemical Or Other Control Methodsmentioning
confidence: 99%
“…Changes in sap‐ingestion behavior are not restricted to neonicotinoids but extend to other plant systemic insecticides, such as the diamide cyantraniliprole, pymetrozine, and other contact insecticides, antifeedants, and the like 125–128 . The antifeedant and growth regulator azadirachtin was one of the earliest targets of EPG research in aphids and leafhoppers, 111,129 along with flonicamid and pymetrozine in aphids, leafhoppers, and psyllids 130,131 . The latter compound, pymetrozine, blocks the transient receptor potential vanilloid (TRPV) channels of chordotonal organs, thus directly and selectively interfering with feeding behavior of sap‐feeding insects, leading to their starvation 132,133 .…”
Section: Perspectives For Pest Managementmentioning
confidence: 99%